1999
DOI: 10.1046/j.1439-0507.1999.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified pellicles on Candida biofilm formation on acrylic surfaces

Abstract: The role of saliva or serum proteins, such as mucin, fibronectin (FN) and mannan-binding protein, on Candida biofilm formation was investigated. Supplementation of saliva with FN had no significant effect on biofilm formation. In contrast, biofilm formation on either mucin-coated or FN-coated acrylic surfaces was significantly less than that of the control. These results suggest that salivary mucin or FN alone does not facilitate biofilm formation of Candida. Supplementation of serum with FN increased biofilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The presence of serum or salivary pellicles, which are normally found in the oral environment and may provide binding sites for Candida (8,10), increased the initial adherence of C. dubliniensis cells to biomaterials and subsequent biofilm formation. Other investigators have previously shown that the presence of serum and salivary pellicles can potentiate C. albicans colonization of acrylic strips and denture lining materials (41)(42)(43)(44)(45)(46). SEM techniques revealed that similar to C. albicans biofilms (5, 23), mature C. dubliniensis biofilms consist of a mixture of yeast and filamentous forms embedded within exopolymeric material.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of serum or salivary pellicles, which are normally found in the oral environment and may provide binding sites for Candida (8,10), increased the initial adherence of C. dubliniensis cells to biomaterials and subsequent biofilm formation. Other investigators have previously shown that the presence of serum and salivary pellicles can potentiate C. albicans colonization of acrylic strips and denture lining materials (41)(42)(43)(44)(45)(46). SEM techniques revealed that similar to C. albicans biofilms (5, 23), mature C. dubliniensis biofilms consist of a mixture of yeast and filamentous forms embedded within exopolymeric material.…”
Section: Discussionmentioning
confidence: 99%
“…The ecologic niche for denture stomatitis, the oral cavity, is similar between rats and humans in terms of salivary flow, host immune response, and host salivary proteins. The role of saliva in Candida adhesion is complex (18,41,42). Saliva has a Compared to other commonly used laboratory animals, we found several advantages to employing a rat for the denture stomatitis model.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cells in the in vitro systems are not exposed to salivary immune components and proteins which may precondition, or coat, the surface and promote adherence. Although several of the host components which play a key role in promoting Candida adherence have been defined, the interaction is likely a complex phenomenon (42). In the denture biofilm niche, additional components hypothesized to impact this growth state include companion oral bacterial flora, contact between the device biofilm and the host mucosal surface, and salivary flow dynamics.…”
mentioning
confidence: 99%
“…Therefore, it has the capacity to reduce biofilm formation and inhibit the synthesis of insoluble polysaccharides in the microbial matrix of the dental biofilm 3,13,14 . This biochemical behavior may be explained by its excellent antimicrobial activity and its clinical effectiveness Antifungal activity of components used for decontamination… 141…”
Section: Discussionmentioning
confidence: 99%
“…for acrylic resin, to which it will adhere and colonize 3,4 . Effective oral and prosthesis hygiene is therefore essential for the maintenance of tissue viability and prevention of denture associated infections 5,6 .…”
mentioning
confidence: 99%